Hubungan Antara Pengetahuan Gizi Balita, Pola Pemberian Makan dan Status Gizi Balita di Puskesmas Pademawu Pamekasan - Primi Octaviana, Lianita; Alief Aidillah, Nurvy; Purmahardini, Nova (NHM PRESS, 2024)
The nutritional status of toddlers is one of the problems that are often faced by countries in the world, especially developing countries such as Indonesia. One of the nutritional problems that are widely encountered in the community such as malnutrition and malnutrition is one of the reasons for the high infant and child mortality rate. The World Health Organization (WHO) noted that there are around 4.5 million children under five, with more than 760,000 of them experiencing malnutrition in Indonesia. The population in this study is all mothers at the Pademawu Health Center who have children under five. There are 200 mothers who have toddlers. a small population of 22 mothers who have children under five at the Pademawu Health Center, Pamekasan Regency. This research was carried out in January-February 2024. The results of the study showed that most of the children under five at the Pademawu Health Center, Pamekasan Regency had good nutritional status (90.9%). The good knowledge about feeding patterns in toddlers (59.09%). The results of the analysis of the research data showed that there was a significant relationship between knowledge about feeding patterns and the nutritional status of toddlers in the Pademawu Health Center Area, Pamekasan Regency in 2024 (p value: 0.004).